In situ grown nickel selenide on graphene nanohybrid electrodes for high energy density asymmetric supercapacitors. Issue 43 (31st October 2018) - Kirubasankar, Balakrishnan; Murugadoss, Vignesh; Lin, Jing; Ding, Tao; Dong, Mengyao; Liu, Hu; Zhang, Jiaoxia; Li, Tingxi; Wang, Ning; Guo, Zhanhu; Angaiah, Subramania
Abstract : A NiSe–G∥AC asymmetric supercapacitor with both pseudocapacitance and EDLC mechanisms provides an energy density of 50.1 W h kg −1 and a power density of 816 W kg −1 . Abstract : Nickel selenide (NiSe) nanoparticles uniformly supported on graphene nanosheets (G) to form NiSe–G nanohybrids were prepared by an in situ hydrothermal process. The uniform distribution of NiSe on graphene bestowed the NiSe–G nanohybrid with faster charge transport and diffusion along with abundant accessible electrochemical active sites. The synergistic effect between NiSe nanoparticles and graphene nanosheets for supercapacitor applications was systematically investigated for the first time. The freestanding NiSe–G nanohybrid electrode exhibited better electrochemical performance with a high specific capacitance of 1280 F g −1 at a current density of 1 A g −1 and a capacitance retention of 98% after 2500 cycles relative to that of NiSe nanoparticles. Furthermore, an asymmetric supercapacitor device assembled using the NiSe–G nanohybrid as the positive electrode, activated carbon as the negative electrode and an electrospun PVdF membrane containing 6 M KOH as both the separator and the electrolyte delivered a high energy density of 50.1 W h kg −1 and a power density of 816 W kg −1 at an extended operating voltage of 1.6 V. Thus, the NiSe–G nanohybrid can be used as a potential electrode material for high-performance supercapacitors.